STRATEGI PEMENANGAN PARTAI DEMOKRASI INDONESIA PERJUANGAN DALAM UPAYA MENDAPATKAN KURSI DEWAN PERWAKILAN RAKYAT DAERAH DI KABUPATEN ROKAN HILIR PADA PEMILIHAN LEGISLATIF TAHUN 2019 - Ar, Badra Aprizasa; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Political parties cannot give up power, interests, and also position, to achieve this all political parties need a strategy to win contestation or succession in every political event such as regional elections, legislative elections, or elections. This can also be seen from the Indonesian Democratic Party of Struggle to be able to get the most votes in the 2019 Legislative Election in Rokan Hilir Regency. Rokan Hilir Regency. The purpose of this research is to describe the winning strategy of the PDIP party in preparation for the legislative election and to describe the factors that influence the strategy of the PDIP party is competing for seats in the DPRD Rokan Hilir Regency.This study uses a qualitative approach with descriptive methods. In the data interview, the writer used techniques and documentation. The results of this study found that the winning strategy of the Indonesian Democratic Party of Struggle in obtaining the most votes in the 2019 legislative elections in Rokan Hilir Regency used a Defensive and Offensive strategy, then it has achieved maximum results but is not by what has been arranged, where the parties are 9 group seats in the upcoming regional head elections can carry a single candidate without a coalition with other parties, but the results obtained are only a few seats.  Keywords: Winning Strategy, Legislative Election, Strategy, Factors